2011
DOI: 10.1186/1471-2458-11-909
|View full text |Cite
|
Sign up to set email alerts
|

Appreciation and implementation of the Krachtvoer healthy diet promotion programme for 12- to 14- year-old students of prevocational schools

Abstract: BackgroundKrachtvoer is a school-based healthy diet programme, developed in 2001 and revised in 2007 to meet the needs of particular segments of the target population as well as a wider target group. The main aims of the present process evaluation of the revised programme were to examine student and teacher appreciation of the programme, completeness of and adherence to its implementation, and relations between appreciation and completeness of implementation.MethodsData were collected among 22 teachers and 111… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
43
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 27 publications
(44 reference statements)
0
43
0
Order By: Relevance
“…Additional optional programme elements within lesson 4 (second part) and lesson 7 (first part) are participating in a nationwide recipe contest (as homework), reading and discussing the Krachtvoer magazine, knowledge tests on the programme website, and additional food exposure activities as proposed in lesson 5. The programme builds on the three phases of selfmanagement theory (13) , successively aiming at raising awareness of personal dietary intakes, proposing solutions in order to meet the Dutch dietary guidelines and setting personal goals for dietary improvement (10,14) . A programme overview is presented in Box 1.…”
Section: Content Of the Programmementioning
confidence: 99%
See 1 more Smart Citation
“…Additional optional programme elements within lesson 4 (second part) and lesson 7 (first part) are participating in a nationwide recipe contest (as homework), reading and discussing the Krachtvoer magazine, knowledge tests on the programme website, and additional food exposure activities as proposed in lesson 5. The programme builds on the three phases of selfmanagement theory (13) , successively aiming at raising awareness of personal dietary intakes, proposing solutions in order to meet the Dutch dietary guidelines and setting personal goals for dietary improvement (10,14) . A programme overview is presented in Box 1.…”
Section: Content Of the Programmementioning
confidence: 99%
“…A programme overview is presented in Box 1. A more extensive programme description is published elsewhere (10) .…”
Section: Content Of the Programmementioning
confidence: 99%
“…Implementation intentions specify the when, where and how of responses leading to goal attainment. Several studies have focused on implementation intentions and changing people's existing eating behaviour (8)(9)(10)(11)(12)(13)(14) , physical activity behaviour (15)(16)(17)(18) and weight-loss behaviour (19) . Furthermore, some clinical studies have been conducted on implementation intentions regarding eating behaviour or physical activity behaviour among cardiac patients (20,21) and hypertensive patients (22) .…”
mentioning
confidence: 99%
“…This is due to the increased awareness that if health promotion programs are not implemented systematically, their impact on public health will remain low (Durlak & DuPre, 2008;Glasgow et al, 2012;Steckler & Linnan, 2002). It has been established that programs are more likely to be successful if implemented completely and as prescribed by program developers (Bessems et al, 2011;Durlak & Dupre, 2008;Payne, 2009;Payne, Gottfredson, & Gottfredson, 2006). Variability in implementation is related to variability in achieving expected program outcomes (Lendrum & Humphrey, 2012;Little, Riggs, Shin, Tate, & Pentz, 2015).…”
Section: Importance Of Implementationmentioning
confidence: 99%
“…Moreover, a limited number of studies have been reported, describing a systematically developed theory-and evidence-based implementation strategy, targeting each stage of the implementation process and considering the broader environment in which the behavior takes place. Effective implementation strategies nonetheless, are worth looking into as they often lead to maximum effect by ensuring that effective programs are adopted on a large scale, implemented with high levels of fidelity and completeness and continued in the long term (Glasgow, Vogt, & Boles, 1999;Bessems et al, 2011). Designing interventions based on theory and evidence can protect against Type 3 error: failure to produce effective results due to poor design or implementation (Dobson & Cook, 1980).…”
Section: Importance Of Implementationmentioning
confidence: 99%